Designation of a neotype and paraneotype for Conularina triangulata (Raymond, 1905) (Upper Ordovician, eastern North America). (July 2020) - Van Iten, Heyo; Cournoyer, Mario E.; Coyne, Michelle
Abstract : Conularina triangulata (Raymond, 1905), the genotype of Conularina Sinclair, 1942, is a rare, early Late Ordovician conulariid (Cnidaria, Scyphozoa; Van Iten et al., 2006) having three sides or faces instead of four (Sinclair, 1942, fig. 9; Van Iten, 1992, text-fig. 3E). Originally described from the Valcour Formation (early Sandbian; Dix et al., 2013) on Valcour Island, New York (Sinclair, 1942), C . triangulata has since been found in laterally equivalent strata of the upper Laval Formation ('Upper Chazy'; Sinclair, 1942) in Laval, Québec, Canada (Sinclair, 1942). From this same unit and area, Sinclair (1942) erected three new, four-sided species of Conularina ( C . irrasa, C . raymondi, and C . undosa ), and he erected a single four-sided species ( C . narrawayi ) from the Ottawa Formation (now the Sandbian–Katian Ottawa Group; Dix et al., 2013) at Tétreauville (now Gatineau), Québec. Subsequently, Jerre (1994) reported the occurrence of two species of Conularina in the Upper Ordovician of Sweden. Jerre (1994) also proposed that Eoconularia ? forensis Sinclair, 1946 from the Upper Ordovician Citadelle Formation ('Quebec City' Formation; Sinclair, 1946) in Québec City, Québec (Promontoire de Québec thrust sheet, Appalachian Humber Zone, Allochtonous Domain; Castonguay et al., 2002) is a species of Conularina .